Application of Three-Dimensional Imaging to the Intestinal Crypt Organoids and Biopsied Intestinal Tissues - Yun Chen; Ya-Hui Tsai; Yuan-An Liu; Shih-Hua Lee; Sheng-Hong Tseng; Shiue-Cheng Tang (The Scientific World Journal)
Two-dimensional (2D) histopathology is the standard analytical method for intestinal biopsied tissues; however, the role of 3-dimensional (3D) imaging system in the analysis of the intestinal tissues is unclear. The 3D structure of the crypt organoids from the intestinal stem cell culture and intestinal tissues from the donors and recipients after intestinal transplantation was observed using a 3D imaging system and compared with 2D histopathology and immunohistochemistry. The crypt organoids and intestinal tissues showed well-defined 3D structures. The 3D images of the intestinal tissues with acute rejection revealed absence of villi and few crypts, which were consistent with the histopathological features. In the intestinal transplant for megacystis microcolon intestinal hypoperistalsis syndrome, the donor’s intestinal tissues had well-developed nerve networks and interstitial cells of Cajal (ICCs) in the muscle layer, while the recipient’s intestinal tissues had distorted nerve network and the ICCs were few and sparsely distributed, relative to those of the donor. The 3D images showed a clear spatial relationship between the microstructures of the small bowel and the features of graft rejection. In conclusion, integration of the 3D imaging and 2D histopathology provided a global view of the intestinal tissues from the transplant patients.